The Influence of the Prevalence of Generation Z and Millennial Age Groups on the Neuroticism Personality Trait: Implications for Employee Performance at the Education Office of Garut Regency - Bulan Tati Fitria; Vicky Achmad Zulfikar (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2025)
This study aims to analyze the influence of Generation Y and Generation Z characteristics on personality neuroticism and its implications for employee performance at the Garut District Education Office. Differences in generational traits, technological adaptation patterns, and work orientations are considered as factors that shape variations in neuroticism within the workplace. A quantitative approach was employed using a four-point scale questionnaire, and the data were analyzed using Structural Equation Modeling (SEM) with 340 respondents. The findings indicate that Generation Y tends to exhibit greater emotional stability, which helps suppress neuroticism, whereas Generation Z shows higher vulnerability to anxiety and pressure, leading to increased neuroticism. In addition, neuroticism serves as a significant mediator linking generational characteristics to employee performance. These results highlight the importance of understanding psychological dynamics across generations to support decision-making in public sector human resource management.